Chemical study of the metal-rich globular cluster NGC 5927. Issue 4 (14th November 2017) - Mura-Guzmán, A; Villanova, S; Muñoz, C; Tang, B
Abstract: Globular clusters (GCs) are natural laboratories where stellar and chemical evolution can be studied in detail. In addition, their chemical patterns and kinematics can tell us to which Galactic structure (disc, bulge, halo or extragalactic) the cluster belongs to. NGC 5927 is one of most metal-rich GCs in the Galaxy and its kinematics links it to the thick disc. We present abundance analysis based on high-resolution spectra of seven giant stars. The data were obtained using Fibre Large Array Multi Element Spectrograph/Ultraviolet Echelle Spectrograph (UVES) spectrograph mounted on ut2 telescope of the European Southern Observatory. The principal objective of this work is to perform a wide and detailed chemical abundance analysis of the cluster and look for possible Multiple Populations (MPs). We determined stellar parameters and measured 22 elements corresponding to light (Na, Al), alpha (O, Mg, Si, Ca, Ti), iron-peak (Sc, V, Cr, Mn, Fe, Co, Ni, Cu, Zn), and heavy elements (Y, Zr, Ba, Ce, Nd, Eu). We found a mean iron content of [Fe/H] = −0.47 ± 0.02 (error on the mean). We confirm the existence of MPs in this GC with an O–Na anti-correlation, and moderate spread in Al abundances. We estimate a mean [α/Fe] = 0.25 ± 0.08. Iron-peak elements show no significant spread. The [Ba/Eu] ratios indicate a predominant contribution from SNeII for the formation of the cluster.